Matching of Investment Opportunities with Potential Investors/Financial Models in AICCRA Countries - Chabot, Philippe; Derenoncourt, Marie Ena; Wamicwe, Peter; Jaquet, Stephanie; Sani, Ouma; Gaba, Morgan; Kouakou, Pierre; Grosjean, Godefroy; Newman, Richard (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
This paper provides an overview of the post-accelerator technical assistance program of the Gender Smart Accelerator Challenge (GSAC). It outlines the support and capacity building approaches to enable the accelerator participants to obtain private sector funds matching the grants awarded by AICCRA. The paper describes the process and activities that were executed, provides details on the results of the program, and finally provides a discussion of results and lessons learned that might be used for the design of future programs of this type.